Pelvis and hind limb muscles reconstruction in the well preserved pseudosuchian Batrachotomus kupferzellensis - Lecuona, Agustina (2019)
Most fossil vertebrates are known by their hard-tissues, but inferring their soft-tissues is important to elaborate a bigger picture of them. Muscular recosntructions in fossil vertebrates are mostly focused on mammals and dinosaurs, whereas two such studies were recently performed within the crocodilian-lineage of archosaurs, in the pseudosuchians Poposaurus and Prestosuchus.